Monster summer [videorecording (DVD)] - Uliano, Cornelius, 1985-; Schulz, Bryan; Thames, Mason, 2007-; Bracco, Lorraine, 1955-; Gibson, Mel; Lerner, Julian; Witherspoon, Abby James; Cottrell, Noah; Zehetner, Nora, 1981-; Renna, Patrick, 1979-; James, Kevin, 1965- (Distribution Solutions, 2025)
When a mysterious force begins to disrupt their big summer fun, Noah and his friends team up with a retired police detective to embark on a monstrous adventure to save their island.